ADVOKAT DAN AKSES TERHADAP KEADILAN: PENGUATAN PERADILAN YANG SEDERHANA, CEPAT, DAN BIAYA RINGAN DI PENGADILAN AGAMA - Arya Apriansyah; Muh. Reza Zulfikar; Safaruddin Safaruddin; Rahman Rahman (Jurnal Risalah Addariyah: Studi Ilmu-Ilmu Keislaman, Pendidikan dan Sosial Kemasyarakatan, 2026)
This research aims to examine the optimization of the role of advocates in ensuring the implementation of the principles of simple, fast, and low-cost trial within the Religious Court system. These principles are fundamental to the Indonesian judicial system as regulated under Law Number 48 of 2009; however, in practice, they still face various obstacles such as convoluted processes, lengthy case resolutions, and high costs. This research employs a normative-empirical method, combining literature studies with the author's practical experience as an advocate. The results indicate that advocates hold a strategic role in realizing an efficient judiciary through the preparation of precise legal documents, professional client assistance, and the promotion of dispute resolution through mediation. Furthermore, advocates contribute to reducing litigation costs and accelerating the judicial process by utilizing electronic systems (e-court). Optimizing the advocate's role is determined not only by professional competence but also by integrity, adherence to ethics, and a commitment to providing access to legal aid, including for the underprivileged. Thus, the presence of professional and responsible advocates is key to supporting the realization of simple, fast, and low-cost trial principles and enhancing access to justice for the public.